The Evidence from Nin concerning Bishop Natalis (1436 – 1462), Apostolic Legate to Bosnia / Ninska svjedočanstva o biskupu Natalu (1436. – 1462.), apostolskom legatu u Bosni - Nikola Jakšić (Miscellanea Hadriatica et Mediterranea, 2015)
The article deals with two historical artefacts from the mid-fifteenth century: an episcopal coat of arms, and a large ring with a crest and inscription of Pope Pius II (Enea Silvio Piccolomini). It argues for a direct connection between both artefacts and Bishop Natalis, who carried out his pastoral duties in Nin from 1436 to 1462. The coat of arms used to be set into the wall above the entrance to the former Episcopal Palace, and the ring with a papal crest is a direct testimony of Natalis’ service as an apostolic legate to Bosnia, a responsibility with which he was entrusted during the final years of his life.